Shotgun Metagenomic Analysis for Mucilage in the Surface Waters of the Çanakkale Strait (dardanelles): Metabolic Diversity, Microbial Community Structure and Antibiotic Resistance Genes - Yılmaz, Sevdan; Küçüker, Mehmet Ali; Kahraman, Dilek; Çelik, Ekrem Şanver; Küçüker, Mehmet Ali (My University, 2021)
In this study, we used shotgun metagenome sequencing to examine the metabolic diversity, microbial community structure and diverse antimicrobial resistance genes of mucilage in the surface waters of the Çanakkale Strait (Dardanelles). Mucilage samples were collected in April 2021 from the three different stations of the Dardanelles. The dominant microbial communities at the phylum level were Bacteroidetes (20.06%), Proteobacteria (13.68%), Verrucomicrobia (6.25%), Planctomycetes (3.02%) and Cyanobacteria (2.5%). Metabolic pathway analysis using KEGG (Kyoto Encyclopedia of Genes and Genomes) revealed that most of the genes of mucilage samples were involved in unclassified (73.86%) followed by metabolism (14.45%), genetic information processing (4.16%), environmental information processing (2.57%), cellular processing (1.88%), human diseases (1.61%), and organismal systems (1.47%). The dfrA3 gene was the most prevalent (20.36%) followed by CRP (18.17%), PmrE (14.92%), rpoB2 (11.17%), SoxR (7.49%), AbeS (6.83%), baeR (5.22%), PmrF (3.70%), dfrA22 (2.20%), dfrA26 (1.76%), dfrA20 (1.63%), golS (1.26%), CAT (1.03%), mtrA (1.01%), TMB-1 (0.64%), novA (0.64%), dfrK (0.59%), vanXB (0.48%), dfrG (0.39%), FosC2 (0.31%), and MexA (0.20%) genes. Antibiotic resistance gene (ARG) types mainly included the resistance genes of multidrug (40.19%), trimethoprim (26.93%), polymyxin (18.62%), rifamycin (11.17%), chloramphenicol (1.03%), aminocoumarin (0.64%), beta-lactamase (0.64%), fosfomycin (0.31%), and vancomycin (0.48%). Antibiotic-resistant bacteria in mucilage can adhere to human skin during swimming, fishing, water sports etc., enter the body through the nose and mouth, and transfer genetic information to the bacteria in contact areas in the human body. Therefore, this situation is risky in public health, and necessary precautions should be taken. In the light of these findings, it has been observed that there is a need for more detailed studies in the future.

Bu çalışma da Çanakkale Boğazı yüzey sularındaki müsilajın metabolik çeşitliliğini, mikrobiyal topluluk yapısını ve çeşitli antimikrobiyal direnç genlerini incelemek için shotgun metagenom dizilimi kullandık. Nisan 2021'de Çanakkale Boğazı'nın üç farklı istasyonundan müsilaj örnekleri toplandı. Filum düzeyinde baskın mikrobiyal topluluklar Bacteroidetes (%20.06), Proteobacteria (%13.68), Verrucomicrobia (%6.25), Planctomycetes (%3.02) ve Cyanobacteria (%2.5) olarak belirlendi. KEGG (Kyoto Genler ve Genomlar Ansiklopedisi) kullanılarak yapılan metabolik yol analizi, müsilaj örneklerinin genlerinin çoğunun sınıflandırılmamış (%73.86), ardından sırasıyla metabolizma (%14.45), genetik prosesler (%4.16), çevresel prosesler ( %2.57, hücresel prosesler (%1.88), insan hastalıkları (%1.61) ve organizma sistemleri (%1.47) ile ilişkili olduğunu göstermiştir. dfrA3 geni baskın olup (%20,36), ardından sırasıyla CRP (%18,17), PmrE (%14,92), rpoB2 (%11,17), SoxR (%7,49), AbeS (%6,83), baeR (%5,22), PmrF (%3,70), dfrA22 (%2,20), dfrA26 (%1,76), dfrA20 (%1,63), golS (%1,26), CAT (%1,03), mtrA (%1,01), TMB-1 (%0,64), novA (%0,64), dfrK (%0,59), vanXB (%0,48), dfrG (%0,39), FosC2 (%0,31) ve MexA (%0,20) genleri yer almıştır. Antibiyotik direnç geni (ARG) tipleri, temel olarak çoklu ilaç direnci (%40,19), trimetoprim (%26,93), polimiksin (%18,62), rifamisin (%11,17), kloramfenikol (%1,03), aminokumarin (%0,64), beta-laktamaz (%0,64), fosfomisin (%0,31) ve vankomisin (%0,48) direnç genlerini içeriyordu. Müsilaj yapısında yüksek çoklu antibiyotik direnci ve trimetoprim, polimiksin, rifamisin ve kloramfenikol gibi önemli antibiyotik dirençlerinin bulunması halk sağlığı açısından riskli bir durum olarak değerlendirilebilir. Bu bulgular ışığında gelecekte farklı zamanlarda ve derinliklerden alınacak örneklerle daha detaylı çalışmalara ihtiyaç olduğu gözlemlenmiştir.
Çanakkale Boğazı Yüzey Sularındaki Müsilaj için Shotgun Metagenomik Analizi: Metabolik Çeşitlilik, Mikrobiyal Topluluk Yapısı ve Antibiyotik Direnç Genleri